Respuesta :
Q: (2a-b) * (a-2b)
[tex](2−)(−2)[/tex]
[tex]2(−2)+(−2)(−)[/tex]
[tex]22−4+(−2)(−)[/tex]
[tex]22−4−(−2)⋅[/tex]
[tex]22−4+22−⋅[/tex]
Q: (4x - 2) * (x -4)
[tex](4−2)(−4)[/tex]
[tex]4(−4)−2(−4)[/tex]
[tex]42−16−2(−4)[/tex]
[tex]42−16−2+8[/tex]
[tex]42−16−2+8[/tex]
[tex]42−18+8[/tex]
[tex]42−18+8[/tex]
Hope its help you !!
You are going to want to FOIL both of these (first, outside, inside, last).
(2a-b)(a-2b)
=2a^2-4ab-ab+2b^2
=2a^2-5ab+2b^2
I’ll break it down more with the second equation. Remember that ^2 means squared.
(4x-2)(x-4)
First: 4x*x= 4x^2
Outside: 4x*-4=-16x
Inside: -2*x=-2x
Last: -2*-4=8
Now let’s put the answers together in one equation.
4x^2-16x-2x+8
Now we will combine like terms.
4x^2-18x+8
(2a-b)(a-2b)
=2a^2-4ab-ab+2b^2
=2a^2-5ab+2b^2
I’ll break it down more with the second equation. Remember that ^2 means squared.
(4x-2)(x-4)
First: 4x*x= 4x^2
Outside: 4x*-4=-16x
Inside: -2*x=-2x
Last: -2*-4=8
Now let’s put the answers together in one equation.
4x^2-16x-2x+8
Now we will combine like terms.
4x^2-18x+8